An Empirical Study of Climate Change on Carbon Dioxide Emission in ASEAN 4: Vector Autoregression Exogenous (VARX) Approach - Panji Tirta Nirwana Putra; Lilis Yuliati; Endah Kurnia Lestari (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2019)
Climate change is a phenomenon of environmental damage due to the increased intensity of carbon dioxide emissions in the atmosphere, which causes the surface temperature of the earth. The carbon dioxide emission is a form of environmental degradation caused by economic activities. This study analyzed the relationship of macroeconomic variables and the carbon dioxide emission in each of the four ASEAN countries (Indonesia, Malaysia, the Philippines, and Thailand). The used of macroeconomic variables (GDP, trade openness, energy consumption, and the exchange rate) is shown to explain the carbon dioxide emission. In this study, Vector Auto regression Exogenous (VARX) method is used to analyze the impact of economic activities on the movement of carbon dioxide emissions. The data used time series with a vulnerable time of the year 1981-2013. The estimation results from these studies show that the GDP variable has the greatest contribution to the dynamics of carbon dioxide emissions in each ASEAN 4 countries. This empirical finding suggests that economic activity has an influence on the growth of carbon dioxide emissions.